Manganese carbonyl polydopamine composite scaffold as well as preparation method and application thereof

By using manganyl carbonyl polydopamine composite scaffold in bone defect repair, it is loaded on mineralized decellularized lotus rods to form nanopore structures, solving the problems of scarcity and inflammatory response of bone donors in bone defect repair, and achieving bone differentiation and regeneration enhancement and anti-inflammatory effects.

CN119236181APending Publication Date: 2025-01-03THE SECOND AFFILIATED HOSPITAL TO NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352453.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art has problems such as scarcity of bone donors, size mismatch and immune rejection in bone defect repair, and the polarization of macrophages leads to a local inflammatory response, affecting the regeneration of bone tissue.

Method used

Using a manganese carbonyl polydopamine composite scaffold, a composite scaffold with a nanopore structure was prepared by loading the manganese carbonyl polydopamine complex on a mineralized decellularized lotus rod to form a composite scaffold, regulating the polarization of macrophages and promoting bone differentiation and regeneration.

Benefits of technology

This composite scaffold significantly enhances bone differentiation and regeneration ability, promotes the proliferation and migration of bone marrow mesenchymal stem cells, has anti-inflammatory effects, reduces local inflammation, and improves the effect of bone defect repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236181A_ABST
    Figure CN119236181A_ABST
Patent Text Reader

Abstract

The invention provides a carbonyl manganese polydopamine composite scaffold as well as a preparation method and application thereof. Polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, dopamine hydrochloride, 1, 3, 5-trimethylbenzene, ammonium hydroxide and carbonyl manganese react to prepare a carbonyl manganese polydopamine compound, and then the carbonyl manganese polydopamine compound is loaded on mineralized decellularized lotus stems to prepare the carbonyl manganese polydopamine composite scaffold. By applying the composite scaffold, the bone differentiation and regeneration capability can be effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbonyl manganese polydopamine composite scaffold and a preparation method and application thereof. Background Art

[0002] Reconstruction of large bone defects caused by severe trauma, tumor resection, and congenital malformations has always been a serious problem faced by patients and orthopedic surgeons worldwide. Autologous and allogeneic bone transplantation has become the mainstream strategy for repairing large bone defects in clinical treatment, but the scarcity of bone donors, bone size mismatch, and immune rejection limit its further application. In recent years, bone immunomodulation has become a new strategy to promote bone immune balance by regulating the interaction between immune cells and bone cells. After implantation, scaffolds with good bone immunomodulatory properties activate the immune system and dynamically regulate the bone immune microenvironment in the host under physiological conditions to promote bone integration. Among them, macrophages are one of the most important effector cells in the immune response, which initiates and mediates the host allogeneic response. It is well known that the recruitment of macrophages to the scaffold surface is the main cause of some local acute inflammatory reactions and even a series of chronic inflammations, which have a destructive catabolic effect on bone tissue. In general, macrophages are strategically polarized to the classically activated M1 phenotype, which destroys adjacent bones by producing proinflammatory cytokines or the pro-healing M2 phenotype to reduce inflammation or / and promote osteogenesis. Therefore, regulating macrophage polarization toward M2 is beneficial to reduce local tissue inflammation and create a favorable bone immune microenvironment. Summary of the invention

[0003] Based on this, it is necessary to provide a carbonyl manganese polydopamine composite scaffold and a preparation method and application thereof. The carbonyl manganese polydopamine composite scaffold can enhance bone differentiation and regeneration.

[0004] The present invention adopts the following technical solution:

[0005] The present invention discloses a carbonyl manganese polydopamine composite scaffold, which is prepared by loading a carbonyl manganese polydopamine composite on a mineralized decellularized lotus stem or a freeze-thawed mineralized decellularized lotus stem; wherein the carbonyl manganese polydopamine composite is mainly prepared by reacting polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, dopamine hydrochloride, 1,3,5-trimethylbenzene, ammonium hydroxide and carbonyl manganese. In particular, the carbonyl manganese polydopamine composite scaffold has a nanopore structure.

[0006] The present invention also provides a method for preparing the above-mentioned carbonyl manganese polydopamine composite scaffold, comprising the following steps: preparing decellularized lotus stem, mineralizing and freeze-thawing to obtain freeze-thawed mineralized decellularized lotus stem; preparing a carbonyl manganese polydopamine complex, and loading the carbonyl manganese polydopamine complex onto the freeze-thawed mineralized decellularized lotus stem to obtain.

[0007] In some embodiments, the preparation steps of the decellularized lotus stem include: soaking the lotus stem slices in an SDS solution, then soaking them in a mixture of sodium hypochlorite and Triton X-100, then incubating them in a Tris-HCl buffer, and freeze-drying them.

[0008] In some embodiments, the mineralization is mainly carried out by cross-linking reaction between calcium chloride and the decellularized lotus stem.

[0009] In some of the embodiments, the freeze-thaw process parameters are: freezing at -20°C for 12 hours, then thawing at room temperature for more than 6 hours, and the freeze-thaw cycle is repeated 2 to 3 times.

[0010] In some of the embodiments, the carbonyl manganese polydopamine complex was loaded by freeze-thawing process with PVA hydrogel solution and freeze-thaw mineralized decellularized lotus stem.

[0011] The present invention can also provide the use of the carbonyl manganese-polydopamine composite scaffold in the preparation of a drug or carrier for preventing or treating bone defects.

[0012] The present invention can also provide the use of the carbonyl manganese polydopamine composite scaffold in the preparation of a drug or carrier for enhancing the proliferation and migration behavior of bone marrow mesenchymal stem cells.

[0013] The present invention can also provide a carbonyl manganese-polydopamine composite scaffold for use in preparing anti-inflammatory drugs or carriers.

[0014] Compared with the prior art, the core advantages of the present invention are:

[0015] Through a large number of experimental studies, the inventor team discovered for the first time that the carbonyl manganese-polydopamine composite scaffold prepared by loading the carbonyl manganese-polydopamine complex on mineralized decellularized lotus stems has excellent ability to enhance bone differentiation and regeneration, and can enhance the proliferation and migration behavior of bone marrow mesenchymal stem cells, and has anti-inflammatory effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Figure 1 is the characterization of mPDA and MnCO@mPDA; Figure A is the electron microscope image and energy spectrum test image of mPDA and MnCO@mPDA; Figure B is the lens image and energy spectrum test image of MnCO@mPDA; Figure C is the particle size analysis of mPDA and MnCO@mPDA; Figure D is the Zeta potential test image of mPDA and MnCO@mPDA; Figure E is the Fourier infrared test image of mPDA, MnCO and MnCO@mPDA; Figure F is the XPS test image of mPDA and MnCO@mPDA; Figure G is the statistical graph of CO release ability test; Figure H is the statistical graph of cytotoxicity test of different concentrations of MnCO@mPDA.

[0017] Figure 2 It is the basic characterization of Lotus, DL, MDL, MDL3, and MM@MDL3; among them, Figure A is a physical picture of different materials; Figure B is a cross-sectional electron micrograph of different scaffold materials; Figure C is a longitudinal cross-sectional electron micrograph of different materials; Figure D is an energy spectrum analysis of different scaffold materials; Figure E is a statistical chart of DNA quantification test of Lotus and DL; Figure F is a statistical analysis of protein test of Lotus and DL; Figure G is a statistical chart of porosity of different scaffold materials; Figure H is a long and short diameter analysis of different scaffold materials; Figure IJ is a compressive stress-strain analysis and quantification of different scaffold materials; Figure KL is a tensile stress-strain analysis and quantification of different scaffold materials.

[0018] Figure 3 Biocompatibility tests of DL, MDL, MDL3, and MM@MDL3; Figure A is a cell live / dead staining diagram of different scaffold materials; Figure B is a CCK-8 experimental statistical diagram of different materials; Figure C is a cell activity statistical diagram of different scaffold materials; Figure D is a cell activity statistical diagram of different scaffold materials.

[0019] Figure 4 These are statistical graphs of cell experiment tests for DL, MDL, MDL3, and MM@MDL3; Figures A and D are statistical graphs of cell scratch experiments and quantitative tests of different scaffold materials; Figures B and E are statistical graphs of transwell experiments and quantitative tests of different scaffold materials; Figures C and F are statistical graphs of angiogenesis experiments and quantitative tests of different scaffold materials.

[0020] Figure 5 The results are a test on promoting the osteogenic differentiation of bone marrow mesenchymal stem cells in vitro by DL, MDL, MDL3 and MM@MDL3. Figures A to D are alkaline phosphatase (ALP) staining images and statistical graphs of quantitative test results of ALP activity; Figures EH are statistical graphs of Alizarin red staining (AR) and calcium nodule test results; Figures IL are statistical graphs of qPCR results of COL1, OCN, OPN and RUNX2, respectively.

[0021] Figure 6 The figures are statistical graphs of the experimental results of stem cell recruitment of DL, MDL, MDL3, and MM@MDL3; Figure A is the confocal images of stem cell recruitment of different scaffold materials; Figure B is the quantified violin plot of different scaffold materials; and Figure C is the quantitative trend graph of different scaffold materials.

[0022] Figure 7Figures 1 and 2 are statistical graphs of the polarization function tests of DL, MDL, MDL3, and MM@MDL3 macrophages; Figures AC are CD86 and CD206 fluorescence images and quantitative test statistical graphs of different scaffold materials; Figures DE are ROS fluorescence images and semi-quantitative statistical graphs of ROS inhibition (%).

[0023] Figure 8 Figure 1 is a statistical graph showing the bone regeneration ability test in the rat skull defect model; Figure A is the micro-CT 3D reconstructed images and coronal views of the different scaffold material groups 4 and 8 weeks after surgery; Figure BC is the regenerated bone volume (BV / TV) of the different scaffold material groups 4 and 8 weeks after surgery; Figure DE is the statistical graph of trabecular separation and average trabecular thickness of different scaffold materials 4 and 8 weeks after surgery.

[0024] Fig. 9 The figures are statistical graphs of the histological observation results of bone regeneration; Figures AB are H&E and trichrome staining of decalcified skulls in different scaffold material groups 4 and 8 weeks after surgery; Figure C is a quantitative statistical graph of the newly formed bone area; Figure D is a quantitative statistical graph of the new collagen area stained by Masson.

[0025] Fig.10 Fluorescence staining and quantitative analysis; Figure AB is the CD31 fluorescence staining images and semi-quantitative statistical graphs 4 and 8 weeks after surgery; Figure CF is the CD206 / iNOS fluorescence staining images and semi-quantitative statistical graphs 4 and 8 weeks after surgery.

[0026] Fig.11 These are test diagrams for studying the mechanism of osteogenic differentiation; wherein, Figure A is the fluorescence staining of BMP2; Figure B is the semi-quantitative analysis statistical diagram of BMP2; Figure C is the fluorescence staining of SMAD; Figure D is the semi-quantitative analysis statistical diagram of SMAD; Figure E is the fluorescence staining of RUNX2; and Figure F is the semi-quantitative analysis statistical diagram of RUNX2.

[0027] Fig.12 The statistical charts are for the analysis of signal pathways of different scaffold materials for enhancing bone formation; Figure A and Figure D are the fluorescence staining images of C-FOS, RANKL, HIF-1ɑ, and P85 in tissues 8 weeks after surgery using different scaffold materials, and Figures BF are the semi-quantitative analysis statistical charts of RANKL, C-FOS, P85, and HIF-1α, respectively. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly. The following embodiments are only used to illustrate the present invention, but are not only used to limit the scope of the present invention. Based on the specific embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention. In the embodiments of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the embodiments of the present invention, if not specifically specified, the technical means used are conventional means well known to those skilled in the art.

[0029] Sources of some key experimental materials:

[0030] Lotus stems: all purchased from Yonghui Supermarket (lotus leaves, lotus pods, China).

[0031] Polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate (F127): molecular weight about 15 kDa, purity 98%, analytical grade, purchased from Aladdin.

[0032] Dopamine hydrochloride (DA): purity 98%, analytical grade, purchased from Aladdin.

[0033] Ammonium hydroxide (NH4OH): purity 28-30wt%, purchased from Aladdin.

[0034] 1,3,5-Trimethylbenzene (TMB): purity 98%, analytical grade, purchased from Aladdin.

[0035] Manganese carbonyl (MnCO): purchased from Aladdin (Catalog No.: M189337, Shanghai, China).

[0036] Cell counting kit-8 (CCK-8) was purchased from Beyotime Biotech (Catalog No.: C0040, Shanghai, China), and acridine orange / ethidium bromide staining kit was purchased from Merida Technology (Catalog No.: Shenzhen M247364, China). Anti-CD31 rabbit polyclonal antibody, rabbit polyclonal anti-CD206, rabbit pAb (Catalog No.: ab64693) and mouse monoclonal anti-iNOS antibody (Catalog No.: ab178945) were purchased from Abcam Group. Goat anti-rabbit IgG H&L (Alexa Fluor 594, Catalog No.: ab150080) and goat anti-mouse IgG H&L (Alexa Fluor 488, Catalog No.: ab150113) were purchased from Abcam Group.

[0037] Preparation of PVA hydrogel solution: 5% PVA was placed in pure water, heated to 60°C and stirred for 12 hours until the particles were completely dissolved.

[0038] Preparation of mPDA: 1g of polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate (F127) and 0.5g of dopamine hydrochloride (DA) were dissolved in an ethanol aqueous solution (50mL water and 50mL ethanol), and stirred at 500rpm for 30min; then 2mL of 1,3,5-trimethylbenzene (TMB) was slowly added to the mixed solution, and the mixture was stirred for 30min, and then 5mL of ammonium hydroxide (NH4OH) was injected, reacted for 30min, and ultrasonically dispersed for 1h. The reaction product was centrifuged, washed with water and ethanol until the block polymer was completely removed, and then dried at 60℃ for 12h to obtain mPDA powder.

[0039] Example 1 Preparation of MnCO@mPDA

[0040] This embodiment provides a method for preparing hollow mesoporous polydopamine nanoparticles loaded with manganese carbonyl (MnCO@mPDA), comprising the following steps:

[0041] 1g of polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate (F127) and 0.5g of dopamine hydrochloride (DA) were dissolved in an ethanol aqueous solution (50mL of water and 50mL of ethanol) and stirred at 500rpm for 30min; then 2mL of 1,3,5-trimethylbenzene (TMB) was slowly added to the mixed solution, stirred for 30min, and then 5mL of ammonium hydroxide (NH4OH) was injected. After reacting for 30min, carbonyl manganese (MnCO) with a final concentration of 0.05mg / mL was directly added and ultrasonically dispersed for 1h. The reaction product was centrifuged, washed with water and ethanol until the block polymer was completely removed, and then dried at 60℃ for 12h to obtain MnCO@mPDA powder.

[0042] Example 2 Preparation of DL, MDL, MDL3, and MM@MDL3

[0043] In this embodiment, a specific type of scaffold product is prepared based on lotus stem.

[0044] Preparation of decellularized lotus stem (DL): The lotus stem was cut into 10 mm thick discs, soaked in 10% w / v SDS solution, and placed in a low-speed oscillator at room temperature for 5 days. After 5 days, the sample was washed 3 times with ultrapure water and then soaked in a mixed liquid containing 0.1% Triton-X100 (v / v) and 10% sodium hypochlorite (v / v) for 2 days. Next, the sample was placed in Tris-HCl buffer (pH 8.5) and incubated for 2 days. Finally, the sample was sterilized by soaking in alcohol for 2 hours, then washed 3 times with sterile PBS buffer (pH=7.4), and freeze-dried. The freeze-dried decellularized lotus stem slices were sterilized by ultraviolet for 30 minutes and stored aseptically.

[0045] Preparation of mineralized decellularized lotus stem (MDL): DL was immersed in a 500 mM calcium chloride aqueous solution for cross-linking, and then immersed in a 300 mM potassium hydrogen phosphate aqueous solution and a 500 mM calcium chloride aqueous solution for mineralization, and then placed in ammonia water with a pH of 11 to stabilize the calcium phosphate precipitation, and transferred to PBS buffer (pH 7.4) for at least 5 days to remove unreacted substances to obtain mineralized decellularized lotus stem.

[0046] Preparation of frozen-thaw mineralized decellularized lotus stem (MDL3): DL filled with PVA hydrogel solution (DL was immersed in PVA and kept in vacuum for 12 hours) was placed at -20°C for 12 hours and then thawed at room temperature for more than 6 hours. The freeze-thaw cycle was repeated 3 times, and the mineralization process was repeated (immersed in 500mM calcium chloride aqueous solution for cross-linking, then immersed in 300mM potassium dihydrogen phosphate aqueous solution and 500mM calcium chloride aqueous solution for mineralization, then placed in ammonia water with a pH of 11 to stabilize calcium phosphate precipitation, and transferred to a PBS buffer with a pH of 7.4 for at least 5 days to remove unreacted substances). The resulting product was named MDL3.

[0047] Preparation of freeze-thaw mineralized decellularized lotus stem-carbonyl manganese polydopamine complex (MM@MDL3 or MDL3+MM): Prepare DL containing 50μg / mL MnCO@mPDA (prepared in Example 1) in a PVA hydrogel solution (immerse DL in a PVA hydrogel solution containing 50μg / mL MnCO@mPDA and keep it in vacuum for 12 hours), freeze it at -20°C for 12 hours, and then thaw it at room temperature for more than 6 hours. Repeat the freeze-thaw cycle 3 times, and repeat the mineralization process. The resulting product is named MM@MDL3.

[0048] The above products were characterized and tested for application.

[0049] (1) Fourier transform infrared spectroscopy (FTIR, Thermo Scientific Nicolet iS5), X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha) and X-ray diffraction (XRD, Thermo Scientific K-Alpha) were used for characterization. The internal structure of MnCO@mPDA was observed using scanning electron microscopy (SEM, TESCAN MIRALMS) and transmission electron microscopy (TEM, FEITalos F200S). The particle size distribution was analyzed by dynamic light scattering (DLS) using a nanoparticle size analyzer (Malvern ZetasizerNano ZS90).

[0050] Scanning electron microscopy (SEM) was used to observe the morphology of the prepared scaffolds. EDS was used to characterize the composition of Lotus group, DL group, MDL group, MDL3 group, MM@MDL3 group, and mineralized HAP. FTIR spectroscopy (Thermo Scientific Nicolet 6700) was used to analyze the DL group, MDL group, MDL3 group, and MM@MDL3 group to determine their chemical groups.

[0051] Freeze-dried lotus stem and decellularized lotus stem were immersed in liquid nitrogen and ground into powder, and DNA quantification was performed using a plant genomic DNA kit obtained from Tiangen Biochemical Technology Co., Ltd. (Beijing, China) (DP350). Protein quantification was performed using a plant protein kit obtained from Bestbio Biochemical Technology Co., Ltd. (Shanghai, China). DNA and protein were then measured using a Victor 3 spectrophotometer. DNA and protein concentrations were assessed.

[0052] (2) Biocompatibility

[0053] The cytotoxicity of MnCO@mPDA was evaluated by leaching method and direct contact method. The specific method steps are as follows: the sterilized complex was incubated in culture medium for 24 hours. Bone marrow mesenchymal stem cells (4×10 3 Cells / well) were inoculated in a 96-well plate in regular culture medium for 24 hours, and the culture medium was replaced with 100 μL of filtrate at different concentrations (0, 12.5, 25, 50, 100 μg / mL). On days 1, 3, and 5, 10 μL of CCK-8 reagent dissolved in 90 μL of culture medium was added and incubated for 2 hours. The absorbance was measured at 450 nm and converted to cell activity.

[0054] The cytotoxicity of DL, MDL, MDL3, and MM@MDL3 was evaluated by leaching and direct contact methods. The specific method steps were as follows: the sterilized complex was incubated in the culture medium for 24 hours. Bone marrow mesenchymal stem cells (4×10 3 Cells / well) were seeded in a 96-well plate in regular culture medium for 24 hours, and the medium was replaced with 100 μL of filtrate of DL, MDL, MDL3, and MM@MDL3 (concentration was 1 mg / mL, respectively). On days 1, 3, and 7, 10 μL of CCK-8 reagent dissolved in 90 μL of culture medium was added and incubated for 2 hours, and the absorbance was measured at 450 nm.

[0055] For direct staining, 2 μM calcein AM and 8 μM propidium iodide in PBS were used. After 1 or 3 days in the extraction solution, BMSCs were incubated with the dye (500 μL) at 37°C for 30 minutes. Live cells (green) and dead cells (red) were observed by inverted fluorescence microscopy.

[0056] Hemolysis test: It was performed by isolating red blood cells (RBCs) from rat whole blood mixed with 109mM sodium citrate (ratio of sodium citrate to blood 9:1). The red blood cells were centrifuged at 3000rpm for 5 minutes and washed with PBS buffer. A 5% (volume / volume) red blood cell suspension was prepared. The composite dressing powder was produced by crushing the freeze-dried sample in liquid nitrogen to obtain a 2.5mg / mL dispersion. 0.5 ml of red blood cells were mixed with 0.5 ml of the composite dispersion of different concentrations in a 1.5 ml test tube. After incubation at 37°C for 1 hour and centrifugation at 10000rpm for 10 minutes, 200μL of the supernatant was transferred to a 96-well plate. The absorbance was measured at 562nm (Molecular Devices microplate reader). Deionized water and PBS buffer were positive and negative controls. (n=3)

[0057] Hemolysis (%) was calculated as follows:

[0058] Hemolysis (%) = (Am-Ap) / (Ah-Ap) × 100%

[0059] Where Am is the sample absorbance, Ah is the water absorbance, and Ap is the PBS buffer absorbance.

[0060] (3) CO release detection:

[0061] CO release from the stent was monitored spectrophotometrically by measuring the conversion of Hb to HbCO.

[0062] The specific method steps are as follows: Hb was completely dissolved in PBS buffer and 600 μL of 100 mM sodium dithionite was added. Then, a mixture of DL, MDL, MDL3, and MM@MDL3 scaffolds was introduced to obtain the entire reaction solution, which was immediately sealed in a 4 mL quartz cuvette. A UV-visible spectrophotometer (Lawrenceville, NJ, USA) was used to obtain UV absorption spectra in the range of 350-620 nm at predetermined time points.

[0063] The Beer-Lambert law is used to calculate the amount of CO released using the following equation (1):

[0064]

[0065] Among them, C CO Indicates the concentration of released CO, C Hb is the concentration of Hb (4.56 μm), I 410nm or I 430nm Represents the intensity of the spectra collected at wavelengths of 410 and 430 nm.

[0066] (4) The porosity of the Lotus, DL, MDL, MDL3, and MM@MDL3 groups was measured using the liquid displacement method. The initial weight (m1) and volume (V) of the samples were evaluated, and then the samples were immersed in pure alcohol and the weight (m2) was measured by washing the surface liquid with filter paper until the mass remained constant at room temperature. (n = 3)

[0067] The porosity is calculated as follows:

[0068] Porosity (%) = (m2-m1) / ρV×100%.

[0069] Here, ρ is the density of alcohol.

[0070] (5) The mechanical properties of the DL group, MDL group, MDL3 group, and MM@MDL3 group were evaluated by tensile, shear, and compression tests using an electromechanical universal tester (CMT6104, Mester Industrial). For the tensile test, the sample was stretched at a speed of 2 mm / min until it broke. For the compression test, the sample was compressed at a speed of 2 mm / min to 80% strain.

[0071] (6) In vitro cell migration assay

[0072] HUVECs were seeded in 6-well plates and cultured in high glucose DMEM containing 10% FBS. At 90% confluence, a straight line scratch was made on the cell monolayer using a sterile 1 mL pipette tip. Loose cells were washed away with PBS buffer. The cells were then incubated in serum-free DMEM (control) or serum-free DMEM containing sample extracts for 24, 48, and 72 hours. Phase contrast images were taken at 0, 24, and 48 hours after the scratch. The gap closure rate was quantified using ImageJ software (NIH). HUVECs (1×10 4 Cells / well) were suspended in 100 μL DMEM containing 1% FBS for in vitro transwell migration assay. Cells were seeded into 24-well Transwell plates (Corning) containing Transwell inserts. The lower chamber contained 500 μL of sample (DL, MDL, MDL3, MM@MDL3, at a concentration of 1 mg / mL, respectively) or control medium. After 24 hours of incubation at 37°C and 5% CO2, non-migrated cells were removed from the top of the insert using a cotton swab. The migrating cells below were stained with crystal violet (Beyotime) and imaged under a microscope.

[0073] (7) In vitro angiogenesis assay

[0074] In vitro angiogenesis assays were performed by coating 24-well plates with 300 μL of growth factor-reduced Matrigel (BD Biosciences) and incubating at 37°C for 30 min to solidify. Huvec (2 × 10 4 Cells / well) were seeded on Matrigel matrix and treated with samples (DL, MDL, MDL3, MM@MDL3, 1 mg / mL, respectively) in serum-free DMEM or serum-free DMEM alone (control). After incubation for 6 h at 37 °C and 5% CO2, cells were imaged by microscope (Carl Zeiss) and the number of branch points was quantified using ImageJ software (NIH).

[0075] (8) In vitro antioxidant, ROS scavenging and macrophage polarization assays

[0076] The free radical scavenging activity of DL, MDL, MDL3, and MM@MDL3 was tested and evaluated by DPPH assay. DPPH was mixed with samples in 96-well plates (200 μL reaction volume) and incubated in the dark at room temperature for 30 min. The absorbance was read at 517 nm by UV-visible spectroscopy.

[0077] The inhibition percentage was calculated as follows:

[0078] Inhibition rate (%) = (1-OD sample / OD control) × 100%

[0079] DCFH-DA staining was used to evaluate the scavenging of ROS by the composite dressing. Human dermal fibroblasts and macrophages were treated with samples for 24 hours and then incubated with 0.3mM H2O2 for 30 minutes. Cells were stained with 10 μM DCFH-DA in DMEM at 37°C and 5% CO2 for 20 minutes. Fluorescence was imaged by inverted microscopy. Control groups lacked samples or H2O2 treatment.

[0080] The inflammatory microenvironment was formed by adding 100 ng / mL LPS to the culture medium and incubating for 24 hours. The culture was then co-cultured with the sample for 48 hours. The control group was not treated. Subsequently, 4% paraformaldehyde was added to fix the cells for 15 minutes, rinsed three times with PBS buffer for 5 minutes each time, and then 0.5% Triton was added for permeabilization for 15 minutes, and 5% BSA was added for blocking for 2 hours. The cells were incubated with rabbit anti-CD206 polyclonal antibody (1:200, Abcam) or rabbit anti-INOS polyclonal antibody (1:200, Abcam) at 4°C overnight, and goat anti-rabbit IgG H&L (Alexa Fluor 488) (1:2000, Abcam) or goat anti-rabbit IgG H&L (Alexa Fluor 594) (1:2000, Abcam) was incubated at room temperature for 2 hours. Finally, the cell nucleus was stained with DAPI and observed and photographed with a fluorescence inverted microscope (Leica DMi8).

[0081] (9) In vitro osteogenesis assay

[0082] When the density of adult progenitor cells (MC3T3) was 60%, DL, MDL, MDL3, and MM@MDL3 (at a concentration of 1 mg / mL, respectively) were prepared with osteoinduction medium, and the normal medium was replaced, and the medium was changed every 3 days. After 7 or 14 days of culture, MC3T3 was washed with PBS buffer and fixed with 4% paraformaldehyde at room temperature. After that, the samples were stained with an alkaline phosphatase (ALP) staining kit (Biyuntian Biological Reagent Co., Ltd.) according to the instructions. The cells were observed with an inverted microscope. To quantify ALP activity, after 7 and 14 days of culture, the culture medium was discarded and the cells were incubated with cell culture 0.1% TritonX-100 for 1 minute. Then, the cells were ruptured by repeated freezing and thawing three times. After centrifugation, the suspension was used to evaluate ALP activity using an ALP kit.

[0083] Alizarin red staining: After 14 and 21 days of culture, MC3T3 cells were fixed with 4% paraformaldehyde and stained with an Alizarin red staining kit (Sevier Biotech Co., Ltd.) according to the instructions. The cells were then observed under a microscope. To determine the amount of calcium deposition, 1 mL of 10% cetylpyridinium chloride was added to each well after staining to dissolve the stained calcium nodules. After 1 hour, the absorbance was measured at 490 nm by enzyme labeling.

[0084] Immunofluorescence staining: After 7 days of culture, immunofluorescence staining was performed according to the same method as above. Finally, the cells were observed under a fluorescence microscope, and the fluorescence intensity was semi-quantitatively analyzed by image. To further study the effect on osteogenic differentiation gene expression, MC3T3 was co-cultured with DL, MDL, MDL3, and MM@MDL3 (at a concentration of 1 mg / mL, respectively) for 7 days. RNA was isolated using HiPure Total RNA Trace Kit (Magen, China), and the gene expression of COL1, OPN, OCN, and RUNX2 was analyzed by RT-qPCR.

[0085] (10) Stem cell recruitment experiment

[0086] When the bone marrow mesenchymal stem cells in the dish were cultured to a density of 60%, DL, MDL, MDL3, and MM@MDL3 (at a concentration of 1 mg / mL, respectively) were co-cultured with the cells and cultured at 37°C and 5% CO2. The culture medium was replaced every two days, and the cell-loaded scaffolds were fixed with 4% paraformaldehyde for 15 minutes at a predetermined time point and washed 3 times with PBS buffer. Then, the scaffolds were incubated with DAPI working solution (Biyuntian Biotechnology, Cat. No. C1005) at room temperature for 15 minutes and washed 3 times with PBS buffer. CLSM (Nikon A1, Japan) was used to observe the distribution and migration of cells on the scaffolds, with a z-axis height range of 0 to 500 microns.

[0087] (11) Evaluation of rat skull defect model

[0088] The Sprague-Dawley rats (SPF grade, male, 12 weeks old) used in this experiment were purchased from Changsha Tianqin Biotechnology Co., Ltd. This experiment has been approved by the Research Ethics Committee of Nanchang University (Approval No.: NCULAE-20220928013). The experimental groups included the control group (no material intervention), DL group, MDL group, MDL3 group, and MM@MDL3 group. Each group had 10 samples (10 rats), and 5 samples from 5 rats were collected at 4 weeks and 8 weeks after surgery.

[0089] The procedure was as follows: rats were anesthetized with 3% isoflurane in oxygen for about 2 minutes, and then the rat skull was shaved, disinfected twice with iodine, and cleaned once with 75% ethanol gauze. A sagittal incision was made on the top of the rat skull. The skin, subcutaneous tissue, and periosteum were cut in sequence to expose the calvaria. A critical-sized skull defect (8 mm) was made by using a trephine drill mounted on a dentist's drill. Physiological saline solution was added continuously to reduce thermal injury. The wound was cleaned with saline solution, and the bones were treated differently. The periosteum, subcutaneous tissue, and skin were sutured, and the incision was disinfected with iodine. During the operation, the rats were placed on a heating pad to maintain their body temperature. Rats were euthanized by overdose of anesthesia 4 and 8 weeks after the operation. Rat skull samples were isolated, washed with PBS buffer, and soaked in 4% paraformaldehyde for 3 days, then transferred to 70% ethanol, followed by micro-CT scanning, decalcification (10% EDTA, 4 weeks, room temperature), and histological evaluation.

[0090] CT scanning: Ectopic bone formation and rat calvaria samples were scanned using high-resolution micro-CT (Skyscan 1275, Bruker). Scanning parameters included voltage (50 kV), current (60 μA), and image pixel size (9.0 μm). Bone volume, bone area, trabecular thickness, trabecular number, and trabecular pattern factor were analyzed using CTAn software (Bruker). Micro-CT 3D images of isolated samples were reconstructed by CTvol (Bruker). The surface coverage of regenerated bone was calculated using ImageJ software.

[0091] Rat histological observation: After alcohol gradient dehydration and paraffin embedding, tissue samples were cut into 5 μm thick sections for hematoxylin-eosin (H&E) staining, Masson trichrome staining, and immunohistochemical staining. Trichrome staining was performed according to the manufacturer's standard protocol (Catalog No.: MST-8003, Fuzhou Maixin Biotechnology Development Co., Ltd., China). During immunohistochemical staining, the sections were dewaxed and rehydrated, and then the antigens were extracted in heated citrate buffer (citrate buffer, pH 6.0, 90°C) for 15 minutes. Nonspecific antibody binding was blocked with 10% goat serum albumin solution. After adding the primary antibody, the sections were incubated at 4°C overnight. Then, the corresponding secondary antibody was added and incubated at room temperature for 1 hour. Tissue color development was performed using a DAB horseradish peroxidase color development kit and observed according to the manufacturer's standard protocol (Catalog No.: ZLI-9018, Zhongshan Jinqiao Biotechnology Co., Ltd., China). At each time point, at least five randomly selected fields of view were examined in each group and used to evaluate the average positive intensity. Imagej was used to analyze the relative fluorescence intensity of iNOS, CD206, BMP2, SMAD, RUNX2, HIF-1ɑ, C-FOS, P85, RANKL and CD31, and the fluorescence intensity was compared with the control group.

[0092] The above test results can be found in Figures 1 to 12 . Results are expressed as mean ± standard deviation (SD). Statistical analysis was performed using SPSS 20.0. Graphs were generated in Origin and GraphPad Prism 8.0. Statistical significance was determined by one-way ANOVA. P values ​​less than 0.05 were considered significant. P values ​​are indicated as: *p<0.05, **p<0.01, ***p<0.001, ***p<0.0001.

[0093] like Figure 1 As shown: Under a scanning electron microscope (see Figure 1 Figure A) and transmission microscopy (see Figure 1 The successful preparation of MnCO@mPDA can be seen in Figure B. The energy spectrum scan shows that the elements of mPDA are C, O, and N, while the elements of MnCO@mPDA are C, O, N, and Mn. The particle size analysis shows that the size of mPDA is 255nm, and the size of MnCO@mPDA is 295nm (see Figure 1 C in Figure 1); Zeta potential of mPDA is -0.39±0.16; MnCO@mPDA is -22.17±0.69 (see Figure 1 The synthesis of MnCO@mPDA was further confirmed by Fourier transform infrared spectroscopy (FTIR), and the characteristic peak of carbonyl manganese at 2000cm-1 can be seen in the Fourier spectrum of MnCO@mPDA (see Figure 1 X-ray photoelectron spectroscopy (XPS) spectra showed that MnCO@mPDA contained manganese (as evidenced by the Mn characteristic peak at 641.4 eV in XPS) (see Figure Figure 1 Figure F in the figure).

[0094] mPDA has a high specific surface area and nanopore structure. Due to its strong adsorption capacity and abundant nanopores, mPDA can also produce π-π electron transitions and form hydrogen bonds with molecules, which can greatly improve the loading efficiency of MnCO. The CO release absorption spectrum is shown in Figure 2. Figure 1 As shown in Figure G, as time goes by, the generated carbon monoxide gas combines with hemoglobin, causing the absorbance value of hemoglobin at 430nm to gradually decrease, while the absorbance value of carboxyhemoglobin (the product of carbon monoxide gas combining with hemoglobin) at 410nm gradually increases, indicating the generation of carbon monoxide. In vitro co-culture experiments have shown that MnCO@mPDA has good cell compatibility (see Figure 1 For MnCO@mPDA, rat bone marrow mesenchymal stem cells (rBMSCs) exhibited more than 90% cell viability in the concentration range of 0 to 50 μg / mL.

[0095] like Figure 2 As shown: Figure 2 Figure A shows the actual pictures of lotus stem (Lotus), decellularized lotus stem (DL), mineralized decellularized lotus stem (MDL), freeze-thawed mineralized decellularized lotus stem (MDL3), and mineralized decellularized lotus stem loaded with MnCO@mPDA and frozen and thawed three times (MM@MDL3). Figure 2 Figures B and C in the figure show that all lotus stem scaffolds are composed of uniform large pore structures and small pipe structures in the channel wall through scanning electron microscopy; energy spectrum scanning can show the elemental composition of each component scaffold, see Figure 2 Figure D in . Figure 2 Figures E and F in the figure show that the elution rates of DNA and protein of DL are both above 95%, which meets the standards of decellularized materials.

[0096] Compared with DL, the porosity of Lotus is slightly lower due to cell elution; while the mineralized hydroxyapatite spheres attached to the walls of the MDL, MDL3 and MM@MDL3 pipes reduce the porosity. Lotus stem has a multi-channel porous structure, in which the porosity of DL is 88.66±1.76%, and the porosity of the mineralized one is slightly lower at (67.33±0.88)%, see Figure 2 Figure G in Figure 1. The diameters of the large and small pores of the scaffold are approximately 2000 μm and 130 μm, respectively. Figure 2 H diagram in. Mechanical analysis (see Figure 2 Figure 1 (middle IL) shows that the compressive stress and tensile stress of DL are relatively small, 0.49±0.02MPa and 0.20±0.05MPa, while the compressive stress and tensile stress after mineralization increase significantly to 8.54±0.36MPa and 1.24±0.03MPa, and the compressive stress of the scaffold increases further after three freeze-thaw cycles, reaching 12.04±0.48MPa and 1.41±0.02MPa; the compressive and tensile stresses of the composite scaffold increase slightly after adding MnCO@mPDA.

[0097] like Figure 3 As shown: DL, MDL, MDL3 and MM@MDL3 co-cultured cells have cell viability, and no obvious dead cells were found, see Figure 3 Figure A in Figure 2. CCK-8 assay and cell viability further revealed that the above samples did not affect long-term cell proliferation, see Figure 3 Figures B and C. In addition, DL, MDL, MDL3, and MM@MDL3 did not show obvious hemolysis when cultured in blood.

[0098] like Figure 4 As shown: The fastest wound healing was observed in the MM@MDL3 group compared with the DL, MDL, and MDL3 groups, see Figure 4 Figures A and D in Figure 2. The transwell assay showed that the MM@MDL3 group had more infiltrating cells (136.67±3.18 cells / mm2) compared with the DL group (37.33±1.2 cells / mm2), the MDL group (69±2.3 cells / mm2), the MDL3 group (71±2.3 cells / mm2), and the blank group (31±3 cells / mm2), see Figure 4 In addition, HUVECs treated with MM@MDL3 showed obvious tube formation compared with the DL, MDL, and MDL3 groups. The average number of nodules formed in the MM@MDL3 group (48.5±2) was significantly higher than that in the MDL3 group (28±2), MDL group (26±1), DL group (19±1), and blank group (12±2), see Figure 4 Figures C and F in the figure.

[0099] like Figure 5 As shown: Figure 5 Panels A and B in Figure 2 show that all samples cultured in osteoinductive medium showed positive ALP staining results at all time points. The MM@MDL3 scaffold showed the highest osteogenic capacity after 7 and 14 days of culture, while the MDL and MDL3 scaffold groups showed similar osteogenic effects on MSCs. The quantitative ALP activity values ​​were also consistent with the staining results, see Figure 5 ARS staining was also used to analyze the mineralization stage of osteogenic differentiated MSCs in different groups by staining calcium nodules in red. Figure 5 As shown in Figures E and F, the red color in each group deepened with the passage of culture time, and the highest mineralization level with dense distribution of calcium nodules appeared in the MM@MDL3 group.

[0100] In addition, qRT-PCR assay was performed to reflect the osteogenic gene expression in different scaffold groups ( Figure 5 Figure 1 (I and L in Figure 1). From day 7 to day 14, the expression of Runx2, Col I, and OPN genes increased in MSCs cultured with all scaffolds as the culture time increased. Notably, at each time point, MDL, MDL3, and MM@MDL3 scaffolds significantly upregulated the expression of Runx2, Col I, and OPN genes compared with DL scaffolds, but with different increments, which fully demonstrated the ability of the composite scaffolds to enhance osteogenic differentiation.

[0101] like Figure 6Shown: Confocal 3D reconstruction images showing the vertical migration pattern of BMSCs over time within DL, MDL, MDL3, and MM@MDL3. Initially, one day after seeding, cells were mainly located in the range of 0 to 100 μm, then migrated upward to the range of 200 to 400 μm on day 3, and many cells reached a height of 500 μm on day 7. In addition, quantitative analysis of cell density across different depths of the scaffold revealed a similar trend, with cells mainly concentrated in the bottom layer on day 1, gradually increasing and migrating to the middle layer on day 3, and reaching the top layer on day 7.

[0102] Notably, the proliferation and migration of BMSCs in the MM@MDL3 group were significantly enhanced compared with those in the DL, MDL, and MDL3 groups, indicating that MM@MDL3 could further enhance the proliferation and migration behavior of BMSCs.

[0103] like Figure 7 As shown: In the Blank, DL, and MDL groups, LPS-induced inflammation in RAW264.7 cells resulted in a predominantly M1 macrophage polarization, manifested by high iNOS+ expression. In contrast, RAW264.7 cells treated with MM@MDL3 exhibited increased CD206 expression and M2 macrophage polarization, see Figure 7 AC. 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) was used as a ROS probe, and the green fluorescence intensity was used to assess the ROS level. Figure 7 As shown in Figure D, after H2O2 stimulation, the fluorescence intensity of the MM@MDL3 group was significantly reduced compared with the blank, DL and MDL groups. In addition, the inhibitory effect of MM@MDL3 (61.87±1.63%) on free radicals was significantly stronger than that of DL (26.43±1.35%) and MDL (30.6±1.85%) groups, see Figure 7 Figure E in .

[0104] like Figure 8 As shown: Micro-CT three-dimensional reconstruction images and sagittal images at 4 and 8 weeks after surgery showed that the regenerated bone increased and the surface new bone coverage was higher in the MDL group, MDL3 group, and MM@MDL3 group compared with the control group (Blank) and DL group. Quantitative analysis of regenerated bone (BV / TV, %) showed consistent results, with the highest BV / TV observed in the MM@MDL3 group at 4 and 8 weeks after surgery. In addition, at 4 and 8 weeks after surgery, the quantitative analysis of trabecular separation (Tb.Sp) and trabecular thickness (Tb.Th) in the MM@MDL3 group were higher than those in the other three groups.

[0105] like Fig. 9As shown: Compared with the control group (Blank) and the DL group, the organic bone matrix content of the MDL group, the MDL3 group, and the MM@MDL3 group was higher, see Fig. 9 A. Semiquantitative analysis of the regenerated organic bone matrix showed consistent results, see Fig. 9 Figure C. At 4 and 8 weeks after surgery, the MM@MDL3 group showed the most regenerated organic bone matrix. Trichrome staining images of decalcified femurs at 4 and 8 weeks after surgery and semiquantitative analysis of organic bone matrix showed that the MDL group, MDL3 group, and MM@MDL3 group showed more regenerated collagen matrix at 4 weeks after surgery compared with the control group and DL group, see Fig. 9 Figures B and D in Figure 3. At 8 weeks after surgery, higher regenerated bone matrix was observed in the MDL, MDL3, and MM@MDL3 groups compared with the control and DL groups. At 4 and 8 weeks after surgery, the MM@MDL3 group showed the highest level of regenerated bone matrix.

[0106] like Fig.10 As shown: Compared with the control group (Blank) and DL group, the MDL group, the MDL3 group, and the MM@MDL3 group showed higher CD31 expression levels. MM@MDL3 showed higher CD31 expression levels than the MDL group and the MDL3 group. Then, we examined the local inflammatory response in the defect area. CD206 and CD86 immunofluorescence staining images and semi-quantitative fluorescence intensity analysis showed that 4 weeks after surgery, the MDL group, the MDL3 group, and the MM@MDL3 group had decreased expression of M1 macrophages (CD206) and increased expression of M2 macrophages (CD86) compared with the control group and the DL group. In addition, the expression of M2 macrophages was higher in the MM@MDL3 group compared with the MDL group and the MDL3 group. The M1 / M2 ratio in the control group was greater than 1, indicating that the bone defect was mainly pro-inflammatory. However, the M1 / M2 ratio in the MM@MDL3 group was the lowest, indicating a dominant pro-regenerative immune response in the defect area.

[0107] like Fig.11 As shown: To confirm the mechanism of the pathway on osteogenic differentiation, different scaffold materials were used to co-culture with MSCs. Immunofluorescence staining images of BMP2, SMAD and RUNX2, as well as semi-quantitative analysis of fluorescence intensity showed that the expression of BMP2, SMAD and RUNX2 in the MDL group, MDL3 group and MM@MDL3 group increased compared with the control group (Blank) and DL group. In addition, the MM@MDL3 group showed higher expression levels of the three markers than the MHM group. These findings suggest that the above composite scaffolds can potentially enhance osteogenic differentiation and bone regeneration by upregulating the BMP2 / SMAD / RUNX2 signaling pathway.

[0108] like Fig.12As shown: At the same time, in the tissue sections 4 weeks after the operation, the immunofluorescence staining images of HIF-1a, P85, C-FOS, and RANKL, as well as the semi-quantitative analysis of fluorescence intensity showed that compared with the control group and the DL group, the MDL group, and the MDL3 group, the expression of HIF-1a and P85 in the MM@MDL3 group increased, and the expression of C-FOS and RANKL decreased. This indicates that the above-mentioned composite scaffold can enhance bone differentiation by upregulating the PI-3K / Akt / HIF signaling pathway, while downregulating the RANKL signaling pathway and inhibiting osteoclastogenesis, thereby jointly enhancing bone formation.

[0109] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A carbonyl manganese polydopamine composite scaffold, characterized in that: It is prepared by loading carbonyl manganese polydopamine complex on mineralized decellularized lotus stem; The carbonyl manganese-polydopamine complex is mainly prepared by reacting polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, dopamine hydrochloride, 1,3,5-trimethylbenzene, ammonium hydroxide and carbonyl manganese.

2. The carbonyl manganese polydopamine composite stent according to claim 1, characterized in that: The composite support has a nanopore structure.

3. The method for preparing the carbonyl manganese polydopamine composite scaffold according to claim 1 or 2, characterized in that: The steps include: preparing decellularized lotus stem, mineralizing and freezing and thawing, and obtaining freeze-thawed mineralized decellularized lotus stem; A carbonyl manganese-polydopamine complex is prepared, and the carbonyl manganese-polydopamine complex is loaded onto the freeze-thawed mineralized decellularized lotus stem to obtain the result.

4. The method for preparing the carbonyl manganese polydopamine composite scaffold according to claim 3, characterized in that: The preparation steps of the decellularized lotus stem include: soaking the lotus stem slices in an SDS solution, then soaking them in a mixed solution containing sodium hypochlorite and Triton X-100, then incubating them in a Tris-HCl buffer solution, and freeze-drying them.

5. The method for preparing the carbonyl manganese polydopamine composite scaffold according to claim 3, characterized in that: The mineralization adopts calcium chloride to carry out cross-linking reaction with the decellularized lotus stem.

6. The method for preparing the carbonyl manganese polydopamine composite scaffold according to claim 3, characterized in that: The freeze-thaw process parameters are: freezing at -20°C for 12 hours, then thawing at room temperature for more than 6 hours, and repeating the freeze-thaw cycle 2 to 3 times.

7. The method for preparing the carbonyl manganese polydopamine composite scaffold according to claim 3, characterized in that: Carbonyl manganese-polydopamine complex was loaded by freeze-thaw process with PVA hydrogel solution and freeze-thaw mineralized decellularized lotus stem.

8. Use of the carbonyl manganese-polydopamine composite scaffold according to claim 1 or 2 in the preparation of a drug or carrier for preventing or treating bone defects.

9. Use of the carbonyl manganese-polydopamine composite scaffold according to claim 1 or 2 in the preparation of a drug or carrier for enhancing the proliferation and migration behavior of bone marrow mesenchymal stem cells.

10. Use of the carbonyl manganese-polydopamine composite scaffold according to claim 1 or 2 in the preparation of anti-inflammatory drugs or carriers.